Implementasi Resource Based Strategy Dalam Mencapai Sustainable Competitive Advantage - Rizqi, Firdaus Aditya; Nugroho, Wahyu (Fakultas Ekonomi Universitas Wisnuwardhana, 2020)
Abstract: In supporting infrastructure development and housing needs, cement is one of the more widely used strategic commodities. Improvement of infrastructure and property development in Indonesia is caused by an increase in good economic growth in Indonesia. This is the main attraction for both domestic and foreign investors to further enliven the cement industry in Indonesia. Competition occurs between old players and new players who have plans and are building new factories. In addition to PT X in Indonesia there are also 6 (six) other cement companies and 8 (eight) new companies that will invest in the same field which causes competition among the cement industry players to increase. Facing this development, every company is required to be able to develop and evaluate competitiveness by utilizing existing resources to maintain a sustainable competitive advantage in industrial competition. One way to analyze a company's sustainable competitive advantage is to conduct a resource-based view analysis using the VRIO framework. The purpose of conducting a resource based view analysis is to find out whether resources are owned and managed, including in competitive disadvantage, competitive parity, temporary competitive advantage or sustainable competitive advantage. Based on the results of data analysis and discussion of the results of the study, it can be concluded that the resource-based strategy in supporting the achievement of sustainable competitive advantages in PT X is stated to have been proven. A resource-based strategy that includes financial, physical, organizational, technological, human, innovation and reputation resources described in the conclusion of this study is the result that PT X's resources are an important factor in sustainable competitive advantage. Keywords: resources based strategy, sustainable competitive advantage, intangible resources, tangible resources, VRIO framework